Isolation, characterization, and identification of catalytically active species in the MoO3/SiO2 catalyst during solid acid catalyzed reactions - Kotbagi, Trupti V.; Biradar, Ankush V.; Shubhangi B. Umbarkar; Dongare, Mohan K. (Chemcatchem, 2013)
We report the isolation, characterization, and identification of the catalytically active species formed during various acid-catalyzed reactions if silica-supported MoO3 was used as a catalyst. We have reported previously the synthesis and extensive characterization of the silica-supported MoO3 catalyst prepared by the sol-gel process with ammonium heptamolybdate and ethyl silicate-40 as molybdenum and silica precursors, respectively. The TEM images showed uniformly distributed MoO3 nanoparticles on the high-surface area mesoporous silica support and high acidity (0.9mmolg-1) by using temperature-programmed desorption of ammonia (NH3-TPD) analysis. This catalyst has already shown high activity for various acid-catalyzed reactions. To understand the nature of catalytically active species formed during the reaction, the liquid-phase esterification of acetic acid and ethanol was studied as a probe reaction with very high acid conversion (83%) in 8h. During esterification, the reaction mixture turned blue, which indicated a change in the nature of the catalyst under reaction conditions. These catalytically active species formed in the reaction mixture were isolated and extensively characterized by using FTIR, Raman, powder XRD, BET surface area, NH3-TPD, energy dispersive X-ray, and TEM analysis. The characterization results revealed the insitu formation of silicomolybdic acid on the silica surface in the presence of water, which acts as catalytically active species responsible for the acid-catalyzed reactions.
Keywords: esterification reactions; heterogeneous catalysis; Molybdenum; silicon; sol-gel processes